Challenges of Widowhood among Muslim Women in Kebbe Local Government - Bako, Abubakar (Direct Research Journal of Social Science and Educational Studies, 2024)
The role and status of women in society have been subjects of significant discourse throughout history. Islam, as a faith, has historically emphasized the dignity, honor, and rights of women. However, widows, particularly in Muslim communities, continue to face unique challenges that warrant exploration. This article focuses on the socio-economic and cultural difficulties encountered by Muslim widows in Kebbe Local Government, shedding light on their lived realities and proposing actionable strategies for improvement. Widowhood often brings a dual burden: a loss of social status and diminished economic stability. In many cases, widows find themselves marginalized, struggling to navigate societal expectations while managing their livelihoods. Historically, prior to the advent of Islam, women were often deprived of inheritance rights and treated as possessions rather than individuals with agency. While Islamic teachings advocate for the protection and empowerment of widows, cultural practices and systemic barriers sometimes hinder the realization of these principles. This study examines the specific challenges faced by Muslim widows in Kebbe Local Government, including inheritance disputes, limited access to economic resources, and societal stigmatization. By analyzing these issues through qualitative and contextual lenses, the paper aims to identify gaps in policy implementation and community support structures. Furthermore, it seeks to propose practical solutions that align with Islamic values while addressing contemporary needs. Ultimately, this article underscores the importance of fostering inclusive environments that uphold the dignity and rights of widows. By addressing the socio-economic barriers they face, communities can ensure that widows are not only supported but empowered to lead fulfilling lives.